2021
DOI: 10.21203/rs.3.rs-310648/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associated factors of sexual and gender based violence among female high school students in Debre  Markos Town, North West Ethiopia: an institutionally based cross-sectional study

Abstract: Background: Sexual and gender based violence (SGBV) continues to be a concern of health, sexual and reproductive rights, sustainable peace and development issue that cuts across boundaries, cultural backgrounds and socio-economic groups to touch individuals of every sort around the world. SGBV remains one of the greatest inequalities of our time that takes life, violates the right they are entitled with, and seriously endangers women and girl’s mental and physical wellbeing, as well as sexual and economical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…This study identified the higher risk of GBV among the girls who are studying in higher secondary level, which is supported by the gender gap index 0.659 in 2023. (12) In line to our current study findings, previous studies conducted in Debre Markos Town (13) , Nepal (11) and Ethiopia (14) showed that the prevalence of GBV among girls was 47%, 48% and 47.2% respectively. However, our estimates are relatively lower than the study conducted in Southeast Ethiopia (68.2%) and Northwest Ethiopia (67.7%.4).…”
Section: Discussionsupporting
confidence: 91%
“…This study identified the higher risk of GBV among the girls who are studying in higher secondary level, which is supported by the gender gap index 0.659 in 2023. (12) In line to our current study findings, previous studies conducted in Debre Markos Town (13) , Nepal (11) and Ethiopia (14) showed that the prevalence of GBV among girls was 47%, 48% and 47.2% respectively. However, our estimates are relatively lower than the study conducted in Southeast Ethiopia (68.2%) and Northwest Ethiopia (67.7%.4).…”
Section: Discussionsupporting
confidence: 91%
“…At the time of lock down the prevalence of sexual violence and physical violence was found to be 21.28% and 17.78% respectively. This nding is consistent with a study conducted in Debre Markos city particularly the life time gender-based violence were reported to be 47.0% which exactly a similar result but in terms of sexual violence our study result showed a higher prevalence compared with a study done in Debre Markos city, which was 23.3% and regarding physical violence our result was slightly lower that the results of Debre Markos city which was 39.5% (16). The similarities in life time gender-based violence might be due to the nature of similarities of culture, and social living status of the participants because both of the study areas are from Amhara region and mainly Amhara ethnicity the differences might be due to sample size.…”
Section: Magnitude Of Gender Based Violencesupporting
confidence: 92%
“…All of the studies included in this review and meta-analysis were conducted in Ethiopia's four administrative regions and used a cross-sectional design. There were seven studies in the Southern Nations, Nationalities, and Peoples' Region (SNNPR) [20][21][22][23][24][25][26], four in Amhara [27][28][29][30], three in Oromia [31][32][33], and one in Dire Dawa [34]. The sample size for the primary study ranged from 140 at Debre Markos town in Amhara [27] to 1,199 at eastern Ethiopia in Oromia [31].…”
Section: Details Of Original Studiesmentioning
confidence: 99%